2019
DOI: 10.1002/ep.13316
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of CoZnAl‐layered double hydroxide/graphene oxide nanocomposite for the removal of methylene blue: Kinetic, thermodynamic, and isotherm studies

Abstract: The objective of this study was the synthesis of a novel nanocomposite (CoZnAl‐layered double hydroxide [LDH]/graphene oxide [GO]) to solve the adsorption problem of positively charged pollutants by LDHs. To prepare this nanocomposite, CoZnAl‐LDH and GO were synthesized by coprecipitation and modified Hummers methods, respectively. After ultrasonic pretreatment, they were combined to produce CoZnAl‐LDH/GO nanocomposite with a smooth and uniform texture which used to remove methylene blue as a cationic model po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Fourier-transform infrared (FTIR) spectroscopy was employed to investigate the surface functional group in the as-synthesized composites, as represented in Figure B. The FT-IR spectrum of the GO sample reveals characteristic peaks centered at 3700–3200, 1734, 1622, 1398, 1217, and 1051 cm –1 , which could be ascribed to the ν OH mode of the O–H groups, CO, skeletal ring stretch, O–H deformation, C–OH stretching, and C–O–C (epoxy group) stretching vibrations. The peaks arising at 1110 and 607 cm –1 in the sample MnO 2 /GO could be attributed to Mn–O–H and Mn–O vibrations, respectively. , Such hallmarks could be observed in the AgNPs/MnO 2 /ErGO sample, implying the successful synthesis of the desired material. Furthermore, the sample AgNPs/MnO 2 /ErGO witnesses a remarkable decrease in the intensity of the broad peak centering in the region of 3700–3200 cm –1 , suggesting the transformation of GO into rGO nanosheets.…”
Section: Resultsmentioning
confidence: 99%
“…Fourier-transform infrared (FTIR) spectroscopy was employed to investigate the surface functional group in the as-synthesized composites, as represented in Figure B. The FT-IR spectrum of the GO sample reveals characteristic peaks centered at 3700–3200, 1734, 1622, 1398, 1217, and 1051 cm –1 , which could be ascribed to the ν OH mode of the O–H groups, CO, skeletal ring stretch, O–H deformation, C–OH stretching, and C–O–C (epoxy group) stretching vibrations. The peaks arising at 1110 and 607 cm –1 in the sample MnO 2 /GO could be attributed to Mn–O–H and Mn–O vibrations, respectively. , Such hallmarks could be observed in the AgNPs/MnO 2 /ErGO sample, implying the successful synthesis of the desired material. Furthermore, the sample AgNPs/MnO 2 /ErGO witnesses a remarkable decrease in the intensity of the broad peak centering in the region of 3700–3200 cm –1 , suggesting the transformation of GO into rGO nanosheets.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of dodecyl sulfate anions remarkably enhanced the affinity of organic/Zn–Al LDHs due to electrostatic attractions between the adsorbate and the surfactants. Similarly, Sharifi et al prepared a CoZnAl-LDH/graphene oxide (GO) nanocomposite via ultrasonic mixing, addressing the challenge of adsorbing positively charged pollutants by LDHs . Wang et al demonstrated a synthetic compound, MgNiCo-LDH@ ZIF-67, as an adsorbent for Congo Red (CR) in water.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of the significance of water quality and rising utilities of nanotechnology, efforts have been made to discuss different types of water treatment by adsorption using nanoadsorbents 15–17 . LDHs consist of positively charged metallic layers, negatively exchangeable anions, and water molecules 18 . Owing to their unique advantages, such as tunable layers and exchangeable anions, 19 LDHs with a high adsorption capacity and fast removal rate have been widely employed in phosphate adsorption 20 …”
Section: Introductionmentioning
confidence: 99%